Tailoring of photo-responsive molecularly imprinted polymers on multiwalled carbon nanotube as an enantioselective sensor and sorbent for L-PABE. (8th September 2019) - Sajini, T.; John, Sam; Mathew, Beena
Abstract: The present work is aimed to the fabrication of enantioselective sorbent and sensor for the selective and specific recognition of L-phenylalanine benzyl ester (L-PABE) template molecule in photo-responsive molecularly imprinted polymer (PR-MIP). Here a photo-switchable azo-benzene derivative, 4-[(4-methacryloyloxy)phenylazo]benzoic acid (MPABA) is synthesised and used as the functional monomer. Composites of multiwalled carbon nanotubes (MWCNTs) and imprinted polymer were prepared using 1:4 mol imprinting ratio of L-PABE and MPABA and N, N -ethylene bismethacrylamide (EBMAA) as the crosslinking agent. Conventional bulk MIP and their respective non-imprinted polymers were also synthesised and characterized to investigate the influence of pre-organization of binding sites on the selectivity of L-PABE. The enantioselective sensor is fabricated on platinum working electrode using imprinted and non-imprinted polymers and their electrochemical measurements are investigated using cyclic voltammetry (CV), differential pulse voltammetry (DPV) and elctrochemical impendence spectroscopy (EIS). The platinum modified sensors possess a limit of detection and limit of quantification as 0.2086 μmol L −1 and 0.6953 μmol L −1 respectively. MWCNT-MIPs and MIPs exhibit the largest adsorption capacity towards L-PABE. The synthesised polymers reveal characteristic adsorption features and selectivity towards L-PABE in comparison with its enantiomer analogues. Photo-regulated uptake and release studies of MWCNT-MIP and MIP on L-PABE were also done to determine the photoswitching reversibility of functional monomer.